2018
DOI: 10.1055/a-0590-4992
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Lithium Response in Bipolar Disorder

Abstract: The identification of genetic factors associated with lithium response will be important for (1) better understanding of lithium's mode of action and (2) development of a predictive model for optimization of long-term treatment of bipolar disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 79 publications
1
5
0
Order By: Relevance
“…However, among the offspring of lithiumnonresponsive parents, there was a marginally higher incidence of adjustment disorders, perhaps signifying more vulnerability under stress, as well as a significantly higher incidence of lifetime anxiety and psychotic disorders. This is consistent with findings from genetic and neurobiological studies showing differences between lithium-responsive and lithium-nonresponsive bipolar subtypes (38,39). A recent genome-wide association study found an inverse relationship between genetic loading for psychotic illness risk variants and lithium response in adult patients with bipolar disorder (40).…”
Section: Lifetime Psychopathologysupporting
confidence: 86%
“…However, among the offspring of lithiumnonresponsive parents, there was a marginally higher incidence of adjustment disorders, perhaps signifying more vulnerability under stress, as well as a significantly higher incidence of lifetime anxiety and psychotic disorders. This is consistent with findings from genetic and neurobiological studies showing differences between lithium-responsive and lithium-nonresponsive bipolar subtypes (38,39). A recent genome-wide association study found an inverse relationship between genetic loading for psychotic illness risk variants and lithium response in adult patients with bipolar disorder (40).…”
Section: Lifetime Psychopathologysupporting
confidence: 86%
“…The mood-stabilizing drug lithium is effective for reducing mania events in only about two thirds of patients, with many patients requiring a change in therapy during their treatment due to lack of efficacy or adverse events. 53 Compared with other common neuropsychiatric disorders, relatively little research has addressed the role of altered miRNA expression levels, or pre-miRNA mutations, in bipolar disorder. Indeed, genome-wide association studies on the genetics of bipolar disorder have largely been disappointing.…”
Section: Micrornas In Bipolar Disordermentioning
confidence: 99%
“…While pharmacogenetics has become part of the clinical decision making in some medical fields, such as oncology (Al‐Mahayri, Patrinos, & Ali, 2020; Chan, Law, So, Chow, & Waye, 2020; Joshi, Steiner, Konnick, & Suarez, 2019; Morganti et al, 2019; Wang, Merl, Yang, Zhu, & Li, 2020) and cardiology (Davila‐Fajardo et al, 2019; Zhu et al, 2020), in other settings, such as in psychiatry, it is more utilized as a research and discovery tool (Amare, Schubert, & Baune, 2017; Koromina, Koutsilieri, & Patrinos, 2020; Papiol, Schulze, & Alda, 2018; Pisanu, Heilbronner, & Squassina, 2018; van Westrhenen, Aitchison, Ingelman‐Sundberg, & Jukic, 2020; Yoshida & Muller, 2020). Several challenges still limit the integration of pharmacogenetics in clinical practice (Manchia et al, 2020).…”
Section: Introductionmentioning
confidence: 99%